Clinical performance of direct composite resin restorations in a full mouth rehabilitation for patients with severe tooth wear: 5.5-year results. (September 2021) - Mehta, Shamir B.; Lima, Verônica P.; Bronkhorst, Ewald M.; Crins, Luuk; Bronkhorst, Hilde; Opdam, Niek J.M.; Huysmans, Marie-Charlotte D.N.J.M.; Loomans, Bas A.C.
Abstract: Objectives: To evaluate the 5.5-year performance of direct resin composite restorations, prescribed for patients with severe tooth wear, requiring full-mouth rehabilitation. Methods: A convenience sample of 34 patients were recruited to a prospective trial between December 2010 and June 2013. The participants were provided 1269 full-mouth direct resin composite restorations (Clearfil AP-X) by 5 experienced operators, using the DSO-technique. Treatment resulted in an increase in the vertical dimension of occlusion (VDO). Failure was assessed at three levels. Frequencies of failure were analysed using Kaplan Meier survival curves and the effects of the relevant variables calculated with a multifactorial Cox regression ( p < 0.05). Results: Annual failure rates (for all levels of failure, 'Level 3- ') of ≤ 2.2% and ≤ 2.9% were respectively reported for the anterior and posterior restorations with a mean observation time of 62.4 months. The completion of an anterior restoration with the need for further appointments resulted in significantly more Level 2- & 3- failures. An evaluation of the performance of the premolar and posterior maxillary restorations showed significantly lowered risks of certain types of failures, compared to the molar and posterior mandibular restorations. Conclusions: At 5.5 years, 2.3% of the overall restorations displayed catastrophic, (Level 1) failures. Molar restorations, posterior mandibular restorations and the anterior restorations requiring two further sessions for completion, were associated with significantly higher risks for failure. Clinical significance: Direct resin composite can offer an acceptable medium-term option for the treatment of severe, generalized tooth wear; molar restorations may require higher maintenance.